Evaluation of Usability of C2C Web Site: A Case Study of eBay.com - Salleh, Yuslina (2006)
Due to the rapid change and high competitive of the world market today, people are imperatively to conduct business in the modem and easy way in order to remain competitive and profitable. Web site is popular way of conducting business regarding to get any things via the Internet. Most people are adopted portal initiative to sell their things in order to gain lower cost, and reduce time to market. However, there are many C2C (customer-to customer) web site available but there have no standardize C2C web site to be a practice among them in order to ensure it is a user-centered design. The objective of this paper to evaluate the usability of C2C web site to know whether it is meets customer's requirements as well. This paper presents the review of the literature regarding to the e-commerce, usability model and how to evaluate the usability of the web site, as well as the usability of eBay.com web site.